Biomarkers of progressive lung fibrosis - Khan, Fasihul (2022)
Interstitial lung diseases (ILD) encompass a heterogeneous group of immuno-inflammatory and fibrotic diseases of the lung parenchyma. The most common and severe ILD is idiopathic pulmonary fibrosis (IPF), a chronic progressive fibrotic lung disease of unknown aetiology associated with poor prognosis. A substantial proportion of individuals with ILDs other than IPF also develop progressive fibrosis with clinical, radiological, and genetic similarities, suggesting a shared final common pathway across progressive fibrotic ILDs irrespective of aetiology. Study of shared mechanisms of progression has the potential to aid prognostication, enable a precise approach to therapeutic strategies and allow stratification into clinical trials. Biomarkers are objectively measured and reproducible characteristics that enable stratification of disease phenotypes. The aim of this thesis was to examine and characterise the role of clinical biomarkers in fibrotic lung diseases to enable early identification of progressive fibrotic phenotypes.